Determining approximate Stackelberg strategies in carbon constrained energy planning using a hybrid fuzzy optimisation and adaptive multi-particle simulated annealing technique - Raymond, R. Tan, Prof. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/